Enacting heavy sessional drinking: a multi-sited ethnographic study of young adults’ drinking events and related epidemiology, policy and treatment - Hart, Aaron Charles (Curtin University, 2016)
Taking cues from science and technology studies, this thesis explores how problems associated with the heavy sessional drinking of young adults are currently enacted in significant sites of research, policy and service provision. It demonstrates that alcohol epidemiology, policy initiatives to change ‘drinking culture’, and the clinical science associated with alcohol and other drug treatment erase the effects of socioeconomic disadvantage. With reference to ethnographic data, it proposes a range of alternate formulations.